Education of Medical Professionalism and the Role of Educators of Guilan University of Medical Sciences Iran According to its Residents - Alia Saberi; Shademan Nemati; Saba Fakhrieh Asl; Abtin Heydarzadeh; Ali Fahimi (Kerman University of Medical Sciences, 2013)
Background & Objective: There are many reasons that it is necessary to change the culture educational environment and curriculum of medical education toward addressing and developing the fundamentals of medical professionalism The primary objective of this study was to assess the attitudes of residents about training professionalism in the School of Medicine in Guilan University of Medical Sciences Iran Methods: This descriptive study was conducted on 189 residents of Guilan University of Medical Sciences based on a questionnaire adjusted to culture and ethical issues of Iran in 201112 The reliability and validity of the questionnaire was confirmed The data were analyzed by ttest and using the Stata statistical software Results: In this study 140 residents from 14 fields participated with mean age of 322 ± 449 years More than 50% of residents rated the success of medical professionalism education programs as medium to high More than 40% of them have considered the effect of role model educators in the education of these principles to be great 629% of residents agreed with the theoretical-practical teaching of these principles Conclusion: The degree of success of educational programs in various fields of medical professionalism was acceptable but needs improvement The residents acknowledge that they learn the principles of professionalism from their educators in a hidden educational curriculum but believe that they must also be taught in theoretical and practical units